Sosialisasi dan Pelatihan Budidaya Tanaman Unggul untuk Mendukung Program Kampung Buah - Mahatmayana, I Ketut Manu; Supriadi, Devie Rienzani; Primajaya, Aji; Syabena, Muhammad Farrel; Fadila, Abil; Prastyo, Hadi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Karanganyar Village, Klari Subdistrict, Karawang Regency has vast land and potential for fruit crop development. By utilizing this vast land, a fruit village can be created, thereby increasing the potential to improve the income of the surrounding community. This activity aims to support the creation of a fruit village to improve food quality and the economy of the village community. Methods: A participatory approach through the dissemination of information on superior crops and the planting of fruit trees as parent plants. Results: The presence of superior parent plants with high productivity can meet the needs and improve the economy of the Karanganyar Village community. Conclusions: The community is able to produce food for family and community needs by having highly productive and adaptive parent plants.